2020
DOI: 10.1111/psyp.13550
|View full text |Cite
|
Sign up to set email alerts
|

Time of day differences in neural reward responsiveness in children

Abstract: The Reward Positivity (∆RewP) event‐related potential (ERP), generally quantified as the difference between neural responsiveness to monetary gains (RewP‐Gain) and losses (RewP‐Loss) is commonly used as an index of neural reward responsiveness. Despite the popularity of this ERP component in studies of reward processing, knowledge about the role of state‐related influences on the ∆RewP is limited. The present study examined whether ∆RewP amplitudes may differ based on when during the day they are assessed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…One study in a community adult sample found no difference in the RewP between those with a previous SA and controls without a previous SA ( g = -0.14 – 0.21; Tsypes et al, 2020). An unpublished study with a similar design by the same group also failed to find a difference in the RewP between those with a SA and controls ( g = -0.49 – -0.02; Tsypes & Gibb, 2020). Last, among a sample of adolescents experiencing depression, there was a positive relationship between the RewP and having suicide risk (i.e., experiencing any STB; g = 0.74; Pegg et al, 2020).…”
Section: Resultsmentioning
confidence: 86%
“…One study in a community adult sample found no difference in the RewP between those with a previous SA and controls without a previous SA ( g = -0.14 – 0.21; Tsypes et al, 2020). An unpublished study with a similar design by the same group also failed to find a difference in the RewP between those with a SA and controls ( g = -0.49 – -0.02; Tsypes & Gibb, 2020). Last, among a sample of adolescents experiencing depression, there was a positive relationship between the RewP and having suicide risk (i.e., experiencing any STB; g = 0.74; Pegg et al, 2020).…”
Section: Resultsmentioning
confidence: 86%
“…In the recent version of the same theory [24], Gray and McNaughton have discussed BAS-based RR as well as approach-related behaviors and stimuli that contribute to human decisions, choices, and behaviors. Many investigators have found evidence linking the RR trait to a wide range of health and behavioral outcomes in clinical [22,25,26] as well as community [27] samples. RR is also highly relevant to adolescents' behaviors and risk-taking [9,13,28].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent version of the theory [ 2 ], Gray and McNaughton discussed the contribution of the BAS-based reward sensitivity and approach-related behaviors and stimuli to human behaviors. Many investigators have found evidence regarding the relevance of reward sensitivity, as the main component of approach motivations, to a wide range of health and behavioral outcomes in clinical samples [ 24 , 25 , 26 ], as well as the general population [ 27 ]. These BAS-based reward-sensitivity traits are also relevant to children’s risk behaviors [ 11 , 15 , 28 ].…”
Section: Introductionmentioning
confidence: 99%